Recurrent pigmented villonodular synovitis of the temporomandibular joint - Amanda Allen, DO; Nitu Saran, DO (Radiology Case Reports, 2018)
Pigmented villonodular synovitis is a benign but locally aggressive extra-articular tumor arising from the synovial membrane of tendons and bursae occurring near a joint space. Rarely, pigmented villonodular synovitis can involve the temporomandibular joint, which is emphasized in this paper. Diffuse and localized types have been described in the literature. The diffuse type involves the entire synovial membrane and infiltrates adjacent structures, which tend to be more aggressive and associated with a higher rate of recurrence when compared with the localized type. Keywords: Pigmented villonodular synovitis, Temporomandibular joint